Implementation of the code of professional ethics for Thai civil servants - Chokprajakchat, Srisombat; Sumretphol, Nittaya (Kasetsart Journal of Social Sciences, 2017)
The purpose of this research was to examine the implementation of the 2009 Code of Professional Ethics for Civil Servants B.E. 2552 (the Code). Data were collected by conducting focus groups with executive and operational officials and a survey with a sample group of 5,795 civil servants in 117 agencies. The results showed that the majority of the civil servants recognized the provisions of the Code. Another finding was that the knowledge of the Code was disseminated among the civil servants, staff, and employees; the civil servants were encouraged to comply with the Code, namely, cultivating ethics in new civil servants and providing opportunities for civil servants to participate in activities. However, some problems in the implementation of the Code were found. Additionally, among the agencies there still remain breaches of the Code. In agencies not having assessment of the implementation of the Code, it was found that Code misconduct was higher. Whistle-blower measures should be enforced to enhance implementation of the Code.